Unequal access? Gender and sexual orientation in Ecuador's rental market - Wladimir Zanoni; Hugo Hernández; José Gómez; Judith Brito (Inter-American Development Bank (IDB), 2024)
This paper investigates housing discrimination in Ecuadors rental market against women- led and gay male and lesbian (WGL) families, compared to male-led and heterosexual families. Discrimination in housing markets is a critical quality-of-life issue because it exacerbates social disparities by limiting access to safe neighborhoods, quality services, and economic opportunities for marginalized groups. Using an artifactual field experiment with real estate agents (REAs) in Ecuador, we examine whether discrimination varies by the gender of REAs and explore the underlying mechanisms driving this behavior. Our analysis disentangles the observed discriminatory practices into taste-based prejudice and statistical discrimination (stereotyping). We find that discrimination against WGL families is predominantly driven by stereotypes rather than explicit prejudices. Women-led families are favored, while gay and lesbian families face varying levels of discrimination, with stereotypes significantly influencing REAs decisions. Our work contributes to the literature by providing new evidence on the dynamics of gender and sexual orientation discrimination in a Latin American housing market, evidence that emphasizes the role of stereotyping. These findings have significant policy implications because they highlight the need for interventions that target and dismantle harmful stereotypes to promote equity in housing access.
Keywords: J71; R21; J16; 330; Field experiments; Prejudice; Gender; LGBTQ+